Revitalizing Death Khairat Funds Through Social Entrepreneurship: Insight From Death Khairat Funds Organisations In Malaysia - Nuur Halimatus Sa’adiah Masrukhin; Hartini Mohammad (Universal Publishers, 2026)
Indexed by ERA